Penal populism and prison overcrowding: a vicious cycle in Brazil - Silva, Claudenir Pereira da; Oliveira Filho, Enio Walcácer de (JRG Journal of Academic Studies, 2024)
The article investigates the relationship between penal populism and the overcrowding of the Brazilian prison system through an analysis of penal, criminal procedure, and penal execution laws, correlated with a literature review based on specialized doctrine in criminal sciences and critical criminology. The study examines how penal populism, marked by the creation of harsher laws in response to immediate social demands, directly impacts the actions of the police and operators of the criminal justice system, resulting in an increase in the prison population. This increase exacerbates prison overcrowding and compromises the conditions of serving a sentence, hindering resocialization and increasing recidivism rates, which in turn generates greater risks to public safety. The article concludes that the punitive approach, by prioritizing incarceration and harsher penalties, neglects the adverse effects of prison overcrowding and the need for social reintegration policies, proposing that the adoption of alternative approaches, based on critical criminology, such as decriminalization of low-impact social conduct and restorative justice, may be an effective way to mitigate the identified problems.